The effect of the fraud triangle (pressure, opportunity and justification) on the occurrence of fraud - Edward Zadrach Sawaki; Ferdinandus Christian (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The influence of the fraud triangle (pressure, opportunity and justification) on the occurrence of fraud in Bank Papua. This study first aims to analyze the effect of pressure on fraud partially. Second, to analyze the influence of opportunity on fraud. The third is to analyze the effect of justification on fraud and the fourth is to analyze the influence of the three fraud triangle variables simultaneously or together on the occurrence of fraud with objects on permanent employees of Bank Papua. The research was conducted in five offices each of the Head Office, KCU Jayapura, KC Abepura, KC Sentani and KC Arso. Data collection techniques through primary data through questionnaires and secondary data through literature studies from books, journals and company data. The analysis tool used is a multiple linear regression model using the SPSS version 26 application which is applied to a sample of 89 respondents. The results show that the three independent variables (pressure, opportunity and justification) have an influence on the bound variable (fraud) both partially and simultaneously. And the influence of the three independent variables on the fraud variable is 30.1%.